Language of Strata and Expression in Construction of Sampi Amongst Iban Community in Malaysia - Saripah Banseng; Rosline Sandai; Ciptro Handrianto; Shahid Rasool (International Journal of Education, Information Technology, and Others, 2021)
This study aimed to identify the language of strata and expression in the construction of sampi amongst the Iban community in Sarawak, Malaysia. The descriptive qualitative approach was used to analysed eight cultivation prayers (sampi umai) taken from the book Sampi Enggau Biau arranged by Robert Menua Saleh and Janang Ensiring. Construction of sampi explained by content analysis technique. The finding showed the strata of language in the introduction contained initial call, salutation, and self-recognition. The body of sampi contained purpose, call, statement of offering (piring), commands, and dialogue with gods (Petara). The sampi ended with a blessing prayer. Construction of sampi used expressions of calling, statement, requesting, asking, and answering. The implication of the study showed that the language of strata cannot be fully summarized as the use of language depending on the experience and expertise of the bards. The expression that has been used is affected by the skills of the bard in addressing the language of strata.